Forgotten Legacies: Understanding and Mitigating Historical Human Alterations of River Corridors. Issue 7 (19th July 2019) - Wohl, Ellen
Abstract: Legacies are persistent changes in natural systems resulting from human activities. Legacies that affect river ecosystems can result from human alterations outside of the river corridor, such as timber harvest or urbanization, or from alterations within the river corridor, including flow regulation, river engineering, and removal of large wood and beaver dams. Human alterations of river ecosystems have been occurring for thousands of years in some parts of the world and are now ubiquitous, yet both river scientists and the public may be unaware of the persistent effects of historical activities. Failure to recognize the legacy of historical activities that no longer occur can skew perceptions of river process and form and the natural range of variability in river ecosystems. Examples come from rivers of the Mid‐Atlantic Piedmont and the Pacific Northwest regions of the United States. Mid‐Atlantic Piedmont streams in which legacy sediment accumulated behind now‐abandoned mill dams experienced a complete transformation from wide, shallow, marshy valleys to sinuous rivers lined with tall cutbanks, but the existence and the cause of this river metamorphosis was not widely recognized until the first decade of the 21st century. Rivers of the Pacific Northwest from which large wood was removed have changed during the past century from spatially heterogeneous, multichannel systems closely connected to their floodplains via frequent channel avulsion and lateral migration to single‐thread channels with more homogeneous floodplains and less lateral connectivity. Again, this river metamorphosis has only been recognized within the past two decades. In each of these regional examples, river process and form have changed so substantially that the river ecosystems can be described as having assumed an alternative state. In these and many other examples, the alternative state provides lower levels of ecosystem services such as habitat, biodiversity, and attenuation of downstream fluxes of water, sediment, organic carbon, and nutrients. River management designed to enhance and restore these ecosystem services can be more effective if the continuing effects of these historical legacies are recognized. The grand scientific challenges resulting from historical human alterations of river ecosystems include the following: (1) to recognize the existence of a legacy that continues to affect river ecosystem process and form; (2) to understand the source of the legacy with respect to chronology, type, spatial extent, and intensity of human activities; (3) to understand the implications of the legacy regarding how river process and form and river ecosystem services have changed; and (4) to design management or restoration strategies that can mitigate the loss of river ecosystem services. In summary, the existence of forgotten legacies challenges river scientists to recognize the continuing effects of human activities that have long since ceased and also poses challenges for the application of scientific understanding to resource management. Societal expectations for attractive, simple, stable rivers are commonly at odds with scientific understanding of rivers as dynamic, spatially heterogeneous, nonlinear ecosystems. Knowledge of how human actions, including historical actions that have long since ceased, continue to alter river ecosystems can help to bridge the gap between societal and scientific perceptions of rivers. Key Points: Historical human activities have altered river ecosystems in ways no longer visible Failure to recognize these alterations skews perception of river form and process Effective river management and restoration requires close attention to historical legacies